Efektivitas Inkubator bisnis terhadap pendampingan komunitas usaha: (Studi Kasus di sekolah Tinggi Ilmu Ekonomi Bima) - Chairul Hudaya; Abdul Salam; Firdaus Firdaus (Owner : Riset dan Jurnal Akuntansi, 2023)
The existence of the STIE BIMA business incubator as a facilitation facility in accelerating entrepreneurial growth is expected to be the answer to some of the problems of business partners who will be incubated (tenants). This study aims to determine the effect of Business Incubator Effectiveness on Business Community Assistance with a case study at the Bima University of Economics. This research uses a quantitative descriptive approach. The research population is the entire business community assisted by Inbis STIE Bima totaling 165 groups. The research sample was determined by Stratified random sampling method, amounting to 100 respondents. The results of the study show that there is a significant effect of the effectiveness of the business incubator (Variable X) on assisting the business community (Variable Y) by the STIE Bima business incubator. So that it can be concluded that the effectiveness of the STIE Bima business incubator organization regarding business community assistance also shows evidence that there is significance. This research suggests that there is a need to increase the resource capabilities of the STIE Bima business incubator management team and collaboration with various policy-making stakeholders to support business community assistance.